Trade liberalization and decentralization of state‐owned enterprises: Evidence from China. - Fan, Haichao; Hu, Cui; Lin, Faqin; Wang, Huanhuan (Economic Inquiry, 2022)
This paper examines the relationship between trade liberalization and the probability of state‐owned enterprises (SOEs) being decentralized. We find that tariff cuts for inputs significantly lower the probability of a SOE being decentralized, whereas tariff cuts for outputs raise this probability. We also find that as the distance from a SOE to its overseeing government increases, the effects of input and output tariff cuts on the probability of SOEs decentralization become stronger. Our empirical results are consistent with a simple model in which local governments try to balance the costs of supervising SOEs against the profits extracted from SOEs.